Understanding Contextual Factors Influencing Access to Information for Improved Agricultural Decisions: The Case of Agropastoralists in Kilosa and Monduli Districts, Tanzania - Silayo, Ephraem Epafra (University of Dar es Salaam Library Journal, 2024)
This study examined contextual factors influencing access to agricultural information, for improved agricultural decision-making among agropastoralists in Kilosa and Monduli Districts, Tanzania. Specifically, the paper determined the influence of demographic factors on access to agricultural information, ascertained the contribution of user satisfaction with accessed agricultural information, and found the link between ownership of communication channels and access to information for improved agricultural decision-making. Employing multistage and purposive sampling techniques, 395 participants were selected for the study. Quantitative data were collected through a questionnaire while qualitative data were collected using focus group discussions, interviews, and observation methods. Descriptive analysis using the Statistical Product for Service Solutions (SPSS) was applied to the quantitative data. Pearson’s Chi-square test was computed to determine the statistical significance of the selected variables at p < 0.05. Qualitative data were analysed through content analysis. The study found that demographic characteristics, user satisfaction, information adequacy, household responsibility, and availability of resources influence access to agricultural information for informed decision-making among agropastoralists. It concluded that access to information for agricultural decision-making leads to improved livelihoods. To fulfil agropastoralists’ information needs, they should be aware of these factors and use such awareness to improve access to agricultural information. The study recommends engaging stakeholders through training, social networks, and information portals. Keywords: Access to information, agricultural decision making, agricultural information, agropastoralists income, information needs https://dx.doi.org/10.4314/udslj.v19i2.8